Patterns of Communicable and Non-Communicable Diseases in Pilgrims during Hajj - Mainul, Haque; Nordin, Simbak; Nor Iza, A.Rahman (2014)
Introduction: Hajj is the largest annual gatherings in Islamic world. Hajj pilgrims encounter a great deal of tough physical and mental stress. Overcrowding, extreme temperatures and electrolytes imbalance is common among pilgrims. These factors trigger the increased risk for communicable and non-communicable disease. Objective: The main objective of this study was to determine the patterns of common health problems (CHPs) encountered by pilgrims. Methods: CINAHL, EBSCO Host, PubMed, Google Scholar and Science Direct databases were used to search for articles related to the CHPs faced by the pilgrims which were published from 1998 to 2013. Eligible articles included non-experimental, experimental studies and case reports. The patterns and types of illness among pilgrims have been explored from limited intervention based articles. Only 27 studies were included encompassing with 17, 753 respondents out of 500 articles. Results: The analysis revealed that respiratory diseases (76.2%) were the leading health problems among Hajj-pilgrims followed by skin disease (7.4%), meningococcal disease (3.7%) and heat stroke (3.7%). Conclusion: Respiratory diseases are the most common health problems encountered by Hajj-pilgrims in which influenza gave the highest percentage. However, a definitive conclusion could not be drawn due to lack of existing studies related to this area. The existing evidence was insufficient to support the patterns of illness during mass gathering. Therefore, more studies are advocated to report the incidence of respiratory disease among Hajj-pilgrims.